Readings in international accounting - Blake, John; Hossain, Mahmud (International Thomson Business Press, 1996)
This book is divided into five parts: The International Accounting Environment; Somme Specific National Examples; International Comparisons of Some Specific Accounting Issues; Managerial Issues in International Accounting; and International Financial Markets and International Finacial Analysis.